Kebermaknaan Hidup Individu Yang Pernah Mengalami Kekerasan Pada Masa Anak (Child Abuse) - Sara Palila (Jurnal Psikologi Integratif, 2017)
This study aims to reveal how the meaningful life of individuals who have experienced violence in their childhood. Questions to be answered in this study is how the process and the dynamics of fulfilling the meaning of life in individuals victims of violence in children. This research involved two subjects who experienced violence in different forms. Data collection is done through in-depth interviews on the subject and some significant others who can provide additional data. The research data were analyzed using content analysis method in qualitative approach. The result of analysis shows that the process of fulfilling the meaning of life on the victims of child violence through three pillars, namely freedom of action, the will to live meaningfully, and the meaning of life in which contained the meaning of life purpose. While the source of the meaning of life is derived from the value in attitude, where both subjects choose the attitude of taking the lessons of the tragic events they experienced in the form of violence in childhood. The researcher hopes for further researchers to expand the scope of the research to the extent of the process of forgiveness and how the process of life goals of each subject guides their current lives.